Workload Perception and Social Support to Work Stress of Mental Hospital Nurses - Santosa, Nur'aini Widia; Porusia, Mitoriana (Sarana Ilmu Indonesia (salnesia), 2025)
Nurses working in mental hospitals face a high workload, complex obligations, and potential dangers, so they need adequate socialsupport. This study aimed to determine the relationship between the perception of workload and social support and the level ofwork stress in nurses at RSJD Dr. Arif Zainuddin Surakarta. The study used quantitative methods with observational analyticaldesign and cross-sectional approaches. A total of 159 nurses were selected using incidental sampling techniques. The independentvariables were the perception of workload and social support, while work stress was the dependent variable. The research instrument was in the form of a questionnaire that has been tested for validity and reliability. Data analysis was carried out usingthe Kendall Tau correlation test. The results showed that there was no significant relationship between the perception of workloadand work stress (p-value=0,917), nor between social support and work stress (p-value=0,323). It can be concluded that the perception of workload and the level of social support do not have a significant effect on the work stress of nurses in mentalhospitals. Follow-up research is recommended to explore other factors that may play a role in influencing nurses' work stress.